2021
DOI: 10.1136/bmjspcare-2020-002640
|View full text |Cite
|
Sign up to set email alerts
|

The wish to die and hastening death in amyotrophic lateral sclerosis: A scoping review

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) develops into a life-threatening condition 2 to 4 years after the onset of symptoms. Although many people with the disease decide in favour of life-sustaining measures, thoughts about hastening death are not uncommon.ObjectivesOur aim was to examine the scope of literature on the wish to die in ALS and provide an insight into determinants and motives for different end-of-life options.MethodsWe searched eight databases for English and German publications on death wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 121 publications
0
18
0
Order By: Relevance
“…It is curious that suicide appears to be uncommon in U.S. death certificates, but this may be related to the misclassification of this cause 32 . In addition, some patients elect to withdraw from fluid, nutrition, or ventilatory support as a means of hastening death 33 . In such circumstances, it is possible that death certificates would not include a code for suicide, thereby resulting in an undercount of this cause.…”
Section: Discussionmentioning
confidence: 99%
“…It is curious that suicide appears to be uncommon in U.S. death certificates, but this may be related to the misclassification of this cause 32 . In addition, some patients elect to withdraw from fluid, nutrition, or ventilatory support as a means of hastening death 33 . In such circumstances, it is possible that death certificates would not include a code for suicide, thereby resulting in an undercount of this cause.…”
Section: Discussionmentioning
confidence: 99%
“…137 As an alternative to awaiting a pneumonia or other fatal event, patients with advanced neuromuscular respiratory failure who are ready to die can undergo palliative withdrawal of assisted ventilation under titrated sedation in a hospice facility or at home. [146][147][148][149] Physician-assisted suicide is legally available in several European countries and several states in the US as an alternative for people who are not yet dependent on life support and retain the ability to ingest a fatal combination of prescribed medications themselves. 150 Early in the evolution of advanced disease, engagement of a specialist in palliative care can elicit patient and caregiver stresses and concerns to build a well-informed platform for discussing care options near the end of life.…”
Section: End Of Life Respiratory Carementioning
confidence: 99%
“…A scoping review of the literature on desire for hastened death shows this wish is often due to various factors such as unbearable physical symptoms, psychological distress, existential suffering or for social reasons such as not wishing to be a burden on family. 11 For many, the loss of communication and loss of physical abilities and autonomy that would make them dependent on others affected their desire for hastened death. The review also found that significant others and attitudes of healthcare professionals also have an impact on treatment decisions.…”
Section: The Case Of Motor Neurone Diseasementioning
confidence: 99%
“…Having a less rigid, adaptive coping style, as well as earlier connection to palliative care was associated with better psychological adjustment by the patient. 11 The Erdmann et al 11 also showed that MND/ ALS patients are more inclined to reject invasive treatments such as percutaneous endoscopic gastrostomy, but that culture influenced such healthcare options in various jurisdictions. Many jurisdictions also report a higher incidence of suicide in people with neurological disease, earlier in the illness trajectory while they have the capacity to act, even if not eligible for VAD.…”
Section: The Case Of Motor Neurone Diseasementioning
confidence: 99%